Analysis of Health Seeking Behavior in Hypertension Sufferers - MUTIARA ISKANDAR, PUTRI; Hilmi, Indah Laily; Salman, Salman (Sean Institute, 2022)
A healthy person is not only free of illness or weakness, but also maintains a healthy balance between their mental, physical, and social functions.People who have a disease engage in health seeking behavior in an effort to find relief.The purpose of this study is to ascertain how hypertensive patients seek medical attention.because hypertension is still known as the silent killer up until this point.With a prevalence of 22% of the world's population, hypertension is a non-communicable disease that is one of the leading causes of premature death worldwide.A literature review study with a library of 12 domestic and 1 international journals is the approach taken.The Ministry of Health database and Google Scholar are used for the source search.The pattern of behavior that hypertensive patients exhibit when seeking treatment is described in the literature review's findings.